Carrier multiplication in perovskite solar cells with internal quantum efficiency exceeding 100% - Wang, Yue (2024)
Carrier multiplication (CM) holds great promise to break the Shockley-Queisser limit of single junction photovoltaic cells. Despite compelling spectroscopic evidence of strong CM effects in halide perovskites, studies in actual perovskite solar cells (PSCs) are lacking. Herein, we reconcile this knowledge gap using the testbed Cs0.05FA0.5MA0.45Pb0.5Sn0.5I3 system exhibiting efficient CM with a low threshold of 2Eg (~500 nm) and high efficiency of 99.4 ± 0.4%. Robust CM enables an unbiased internal quantum efficiency exceeding 110% and reaching as high as 160% in the best devices. Importantly, our findings inject fresh insights into the complex interplay of various factors (optical and parasitic absorption losses, charge recombination and extraction losses, etc.) undermining CM contributions to the overall performance. Surprisingly, CM effects may already exist in mixed Pb-Sn PSCs but are repressed by its present architecture. A comprehensive redesign of the existing device configuration is needed to leverage CM effects for next-generation PSCs.